2016
DOI: 10.1016/j.freeradbiomed.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking reduction and cessation on the plasma levels of the oxidative stress biomarker glutathione – Post-hoc analysis of data from a smoking cessation trial

Abstract: Cigarette smoke contains high concentrations of free radical components that induce oxidative stress. Smoking-induced oxidative stress is thought to contribute to chronic obstructive pulmonary disease, cardiovascular disease and lung cancer through degenerative processes in the lung and other tissues. It is uncertain however whether smoking cessation lowers the burden of oxidative stress. We used data from a randomized controlled cessation trial of 434 current smokers for a post-hoc examination of the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 38 publications
9
23
0
Order By: Relevance
“…The results of our study demonstrated interaction effects between MS, DM, smoking, and mtDNA content, in the modulation of ischemic stroke risk. Previously, several studies have reported high oxidative stress levels in patients with MS, patients with DM, and in smokers . We also found significantly negative correlations between mtDNA content with BP, blood glucose, triglyceride, and waist‐hip ratio, which were in line with findings from previous studies .…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study demonstrated interaction effects between MS, DM, smoking, and mtDNA content, in the modulation of ischemic stroke risk. Previously, several studies have reported high oxidative stress levels in patients with MS, patients with DM, and in smokers . We also found significantly negative correlations between mtDNA content with BP, blood glucose, triglyceride, and waist‐hip ratio, which were in line with findings from previous studies .…”
Section: Discussionsupporting
confidence: 92%
“…The current study also observed inverse associations of TTL with current and life‐time history of smoking. In line with this result, a smoking cessation trial showed that plasma levels of total glutathione increased among participants who quit smoking . Moreover, the current study showed that obesity was linked to a lower antioxidant capacity, which has been shown previously by another study .…”
Section: Discussionsupporting
confidence: 91%
“…However, Scoenenberger et al (2011), identified that dyslipidemia and smoking are prevalent in younger myocardial infraction patients (43). Smoking is a risk factor, which plays an important role in early atherosclerosis (44), increases the oxidation of LDL cholesterol, and also damages vasodilatation of coronary endothelium (45). The results of this study showed that most patients smoked cigarettes, which are consistent with Shirashi's (2005) study.…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 87%